2021
DOI: 10.7759/cureus.15587
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Bilateral Thalamic Infarcts Involving the Artery of Percheron in the Setting of COVID-19

Abstract: Wilson et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They also reported a high proportion of large vessel occlusion (33%) whereas small vessel occlusion and lacunar strokes were rare (10%) [4]. Recent studies show cryptogenic cause for stroke in COVID-19-positive patients suggesting an association of stroke with COVID infection [5]. The possible mechanism of stroke in COVID-19 patients is attributed to hypercoagulability, endothelial damage, and excessive cytokine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported a high proportion of large vessel occlusion (33%) whereas small vessel occlusion and lacunar strokes were rare (10%) [4]. Recent studies show cryptogenic cause for stroke in COVID-19-positive patients suggesting an association of stroke with COVID infection [5]. The possible mechanism of stroke in COVID-19 patients is attributed to hypercoagulability, endothelial damage, and excessive cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…Branden et al [5] reported a similar case of AOP infarct with COVID-19 infection and their patient presented with right-sided weakness and third nerve palsy at the onset and was thrombolyzed. In contrast, when our patient first presented, the diagnosis was missed since there was no localized neurological abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…In both instances, the patients were discharged with a favorable mRS. The patient in Wilson et al's case 19 underwent thrombolytic therapy, while Pantovic et al's case 20 was managed with intrahospital anticoagulation due to the COVID-19 diagnosis. The etiology of the infarction in one patient was attributed to a PFO.…”
Section: Special Casesmentioning
confidence: 99%